2021
DOI: 10.7717/peerj.12133
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and structure analysis in root of Casuarina equisetifolia under NaCl treatment

Abstract: Background High soil salinity seriously affects plant growth and development. Excessive salt ions mainly cause damage by inducing osmotic stress, ion toxicity, and oxidation stress. Casuarina equisetifolia is a highly salt-tolerant plant, commonly grown as wind belts in coastal areas with sandy soils. However, little is known about its physiology and the molecular mechanism of its response to salt stress. Results Eight-week-old C. equisetif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 81 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…The results are rather different from those reported for the C. glauca branchlets’ proteome [ 30 ], and metabolome [ 25 , 26 , 27 ], where changes were associated to major physiological changes related to photosynthesis, membrane stability and osmoprotection mechanisms [ 22 , 24 , 25 , 26 , 27 ]. This reinforces the hypothesis that C. glauca has a strong stress-responsive system with an extensive set of constitutive defense mechanisms [ 7 , 43 ] complemented by rapid induction of transcriptional changes at the initial stages of salt exposure [ 37 , 40 ]. Despite the differences associated with the molecular changes imposed during the nodulation process (highlighted above), in both plant groups the top-ten up-regulated DEGs were related to signaling, transport, refolding, and stomatal control ( Table 1 , Table 2 , Table 3 , Table 4 and Table 5 ; Figures S4 and S5 ).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The results are rather different from those reported for the C. glauca branchlets’ proteome [ 30 ], and metabolome [ 25 , 26 , 27 ], where changes were associated to major physiological changes related to photosynthesis, membrane stability and osmoprotection mechanisms [ 22 , 24 , 25 , 26 , 27 ]. This reinforces the hypothesis that C. glauca has a strong stress-responsive system with an extensive set of constitutive defense mechanisms [ 7 , 43 ] complemented by rapid induction of transcriptional changes at the initial stages of salt exposure [ 37 , 40 ]. Despite the differences associated with the molecular changes imposed during the nodulation process (highlighted above), in both plant groups the top-ten up-regulated DEGs were related to signaling, transport, refolding, and stomatal control ( Table 1 , Table 2 , Table 3 , Table 4 and Table 5 ; Figures S4 and S5 ).…”
Section: Discussionsupporting
confidence: 84%
“…75–95 million clean reads comprising ca. 53,000–72,000 unigenes [ 37 ]. Finally, Wang et al [ 40 ] reported ca.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations